Special education for children with disabilities in Malaysia: progress and obstacles - Muhamad Nadhir Abdul Nasir; Alfa Nur Aini Erman Efendi (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
In recent years the inclusion of persons with disabilities has become a development agenda for many countries. One of the channels to achieve inclusivity for this social group is through educational provision for children with disabilities. Malaysia has a long history of providing education for children with various categories of disabilities, especially in terms of primary and secondary education. This study evaluated the progress and status of Malaysia’s special needs education. Three qualitative research methods were used for this research; qualitative systematic review, focus group discussion and interviews. Despite positive development such as the formulation of adapted curriculum for primary students with special needs and an introduction of early detection programmes, a lot more challenges still needed to be acknowledged and surmounted as in the case of adequate appropriate resources, early intervention programmes, essential facilities, readiness and adequate teaching materials all of which underlined the imperative of multi-stakeholder participatory collaboration in planning, implementation, monitoring and impact evaluation.